2011
DOI: 10.1007/s11033-011-1084-8
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK regulates calcium signal-mediated lipid accumulation through changing VDR expression in primary preadipocytes of mice

Abstract: In the present study we have examined whether p38 mitogen activated protein kinase (p38 MAPK) signal pathway interacts with calcium signal on lipid accumulation in primary preadipocytes of mice. The primary preadipocytes were treated with p38 MAPK inhibitor SB203580, blockers and excitomotors of calcium channel for 24 h, respectively. Intracellular triglyceride (TG) content was measured by triglyceride kit and lipid accumulation was determined by Oil Red O staining. Meanwhile, the mRNA expressions of peroxisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…It has been indicated that L-VGCC, an important calcium influx channel in the plasma membrane, is involved in [Ca 2+ ] o -mediated adipogenesis of mice primary preadipocytes [33]. Similarly, we found that L-VGCC blocker Nifidipine prevented the increase of [Ca ] i was found to promote adipogenesis of mice BMSCs [12,26] and to boost the late stage of differentiation and lipid filling in human adipocyte differentiation [34].…”
Section: Discussionsupporting
confidence: 63%
“…It has been indicated that L-VGCC, an important calcium influx channel in the plasma membrane, is involved in [Ca 2+ ] o -mediated adipogenesis of mice primary preadipocytes [33]. Similarly, we found that L-VGCC blocker Nifidipine prevented the increase of [Ca ] i was found to promote adipogenesis of mice BMSCs [12,26] and to boost the late stage of differentiation and lipid filling in human adipocyte differentiation [34].…”
Section: Discussionsupporting
confidence: 63%
“…Others have, however, found that protein levels of CYP27B1 and VDR measured by western blotting were consistent with mRNA levels. 53,56 In conclusion, we found a high prevalence of low VD levels in obese women scheduled for bariatric surgery. We found that AT expresses the enzymes forboth the formation of 25OHD and of the active form, 1,25(OH) 2 D, and for degradation of VD.…”
Section: Discussionmentioning
confidence: 53%
“…Further studies have shown that SOCS2 is a negative regulator of GH signaling, resulting in inhibition of intestinal epithelial cell proliferation, which is induced by GH and IGF-1 (Miller et al, 2004), the negative action of estrogen on GH signaling, which is caused by an upregulation of SOCS2 (Leung et al, 2003), and the blocking of GH-dependent inhibition of neural stem cell differentiation (Turnley, 2005). It is also known that glucocorticoids have negative effects on somatic growth and enhance GH-induced SOCS2 expression in primary hepatocytes (Tollet-Egnell et al, 1999;Sun et al, 2012b), suggesting SOCS2 as the mediator of the negative effects of glucocorticoids on GH action.…”
Section: Discussionmentioning
confidence: 99%